Relationships between outdoor physical activity, health-related quality of life, and sleep in 8-to-12-year-old children: an exploratory study - Zayatz, Callista; Hopko, Olivia; Gambino, Karlie; Paluch, Rocco; Anzman-Frasca, Stephanie; Ferrante, Mackenzie J. (Frontiers in Sports and Active Living, 2025)
Children today are at high risk of chronic disease partially because of a sedentary lifestyle. High levels of physical activity in children have been linked to increased physical and psychological wellbeing and high sleep quality. Further, time spent outdoors has also been linked to overall wellbeing in children. Outdoor physical activities may have additional benefits for children, especially in winter when indoor sedentary time increases. The present online survey study examined relationships between parent reports of 8-to-12-year-old children's (n = 47) general physical activity, hiking frequency, health-related quality of life (a measure of children's physical, psychological, and social wellbeing; HRQoL), and sleep routines in winter 2023. Parent-reported frequency of children's hiking was predictive of their overall wellbeing, where those who hiked more frequently had higher HRQoL scores (ß = 1.20, p = 0.01, R2 = 0.24). More frequent hiking was also related to more consistent bedtime and waking routines (ß = 0.19, p = 0.02, R2 = 0.27; ß = 0.19, p = 0.009, R2 = 0.22). In contrast, overall weekly physical activity level was not predictive of HRQoL scores or sleep. The results support further investigation into hiking as a health promotion intervention for youth.